Peran Tokoh Partai Politik Dalam Pendidikan Politik Bagi Generasi Muda Di Desa Jatipurwo Kecamatan Jatipurno Kabupaten Wonogiri - Tri Handayani, Giris; , Prof. Dr. Bambang Sumardjoko.,M.Pd (2016)
Giris Tri Handayani/ A220120055. ROLE OF POLITICAL PARTIES LEADERS IN EDUCATION POLITICS FOR THE YOUNG GENERATION IN THE VILLAGE JATIPURWO JATIPURNO DISTRICT OF WONOGIRI. Essay. Faculty of Teacher Training and Education. Surakarta Muhammadiyah University in July, 2016. The purpose of this research are: 1) To describe the importance of political education should be given to young people in the village Jatipurwo Jatipurno District of Wonogiri. 2) To describe the efforts of leaders of political parties in conveying political education for young people in the village Jatipurwo Jatipurno District of Wonogiri. 3) To describe response to the political education of the young generation is given by prominent political party in the village Jatipurwo Jatipurno District of Wonogiri. This research includes qualitative research emphasis on observation, interviews, and documentation. The results of this research are: 1) political party leaders wanted to give the young people get insight into the world of politics through political education and political literacy of young generation and is aware of its obligations as a citizen to participate in active politics. 2) political party leaders continue to urge young people to follow the political socialization that is given by prominent political party in the village, party leaders also invited the younger generation went to the field as follows campaigns and to organize the country when the election in the village. 3) a variety of responses regarding the holding of political education will be undertaken by the leaders of political parties in the village, there is an opinion that political education needs to be given to young people to further increase knowledge and develop political awareness and some who prefer other activities than following the socialization of political-education. Keywords: political party leaders, political education, young generation